A landmark-based approach to locate symptom-specific transcranial magnetic stimulation targets of depression - Du, Rongrong; Zhou, Qian; Hu, Tianzheng; Sun, Jinmei; Hua, Qiang; Wang, Yingru; Zhang, Yuanyuan; He, Kongliang; Tian, Yanghua; Ji, Gong-Jun; Wang, Kai (Frontiers in Psychology, 2022)
Abstract Objective: Two subregions of the dorsolateral prefrontal cortex have been identified as effective repetitive transcranial magnetic stimulation (rTMS) targets for the "anxiosomatic" and "dysphoric" symptoms, respectively. We aimed to develop a convenient approach to locate these targets on the scalp. Materials and methods: In a discovery experiment, the two standard targets were precisely identified on 24 subjects using a neuronavigation system. Then, a standard localized approach was developed based on individual scalp landmarks. This “landmark-based approach” was replicated and validated in an independent cohort (N = 25). The reliability of the approach was tested by calculating the correlation of both the inter-rater and intra-rater results. Validity was tested by comparing the mean distance between the standard and landmark-based targets to the TMS spatial resolution (i.e., 5 mm). We further conducted a total of 24 sham rTMS sessions to estimate the misplacement between the coil center and target during a10 minute stimulation without neuronavigation. Results: The parameters of the “landmark-based approach” in the discovery experiment were replicated well in an independent cohort. Using discovery parameters, we successfully identified the symptom-specific targets in the independent cohort. Specifically, the mean distance between the standard and landmark-based targets on the cortex was not significantly larger than 5 mm. However, the standard and landmark-based targets distance exceeded 5 mm in more than 50% of subjects. During the 10 minutes sham rTMS session, the average coil misplacement was significantly larger than 5 mm. Conclusion: The “landmark-based approach” can conveniently and reliably locate the two symptom-specific targets at the group level. However, the accuracy was highly varied at the individual level and further improvement is needed.